Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Gender Roles, Relationships and Social Equity in Post-Harvest Management in Mozambique - FANRPAN (ood, Agriculture and Natural Resources Policy Analysis Network, 2018)
Key Recommendations: 1. Gender and other general policies in the agricultural sector should be revised to reflect clear priorities for lowering post-harvest losses (PHL). 2. Crop scientists should be trained and crop-specific PHM research infrastructure should be developed so that PHM can be included as a research component for all crops. 3. Academic and research units should be located in the field, close to the farmers, so that researchers and/or university students are closer to the beneficiaries. 4. PHM programs, projects, and activities must include information and technology development and dissemination relevant to the end-users, including women, children, the youth, and poorer farmers. 5. PHL should be reduced by increasing access to carts/wheelbarrows and their respective repair kits and to draught animals, repairing critical sections of rural roads, and increasing farmers’ access to bags/sacks that are not infested and in good condition. 6. Reduce PHL along the value chain from farm to plate by extending innovations to some of the socially perceived “female-roles” of PHM. 7. Development and dissemination of PHM innovations must also be part of policies, strategies, and practices to promote a better workload distribution by increasing male participation in labourdemanding PHM activities culturally assigned to women. 8. Since women in polygamous marriages and single mothers are easier to work with when it comes to promoting investment in PHM improvements due to their decision-making power in the households, they should be given priority in work plans. 9. Prioritize female farmers in PHM capacity-building initiatives, because they are the ones who deal with most of the PHM activities. 10. Local tools manufacturers should benefit from incentives to lower the cost for the development of manufacturing, processing, and packaging equipment to make them accessible to women and the poor.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; gender / género

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (Chr. Michelsen Institute, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Reformas de descentralização e serviços públicos agrários em Moçambique: Porquê os desafios persistem? - Forquilha, Salvador (IESE, 2014)
Nos anos 1980, vários países da África subsaariana iniciaram um conjunto de reformas ligadas ao sector público visando, entre outros objectivos, fazer face à crise do Estado, que se manifestava essencialmente em duas dimensões, nomeadamente regulação política e provisão de serviços públicos. Desde então, assistiu-se a três gerações de reformas do sector público (Kiragu, 2002; Crook, 2010). A primeira geração vai dos meados dos anos 1980 aos meados dos anos 1990, com enfoque nos Planos de Ajustamento Estrutural; A segunda geração destacou-se nos meados dos anos 1990, com uma forte componente de assistência técnica aos programas das reformas; Finalmente, a terceira geração das reformas inicia nos finais dos anos 1990 e começos dos anos 2000, marcada pela ligação das reformas com as Estratégias de Redução da Pobreza (no caso de Moçambique os PARPAs e o PARP) e um enfoque na questão da descentralização e melhoria de serviços públicos. Que resultados estas reformas trouxeram em termos de provisão de serviços públicos?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; decentralization / descentralização; ⛔ No DOI found

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Brazil’s cooperation in African agricultural development and food security - Patriota, Thomas Cooper; Pierri, Francesca Maria (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
Brazil’s agricultural cooperation in Africa is shifting from small localised projects to more structured ventures capable of having larger and more durable impacts on African rural development. Nonetheless, it still suffers from in adequate coordination between relevant ministries and other governmental bodies. However, the coexistence of two agricultural development paradigms in Brazil’s cooperation should not be seen as incoherent. Rather, it is a direct reflection of the twotiered structure of Brazil’s agricultural policy framework, with support for agribusiness provided by the Ministry of Agriculture, Livestock and Food Supply (Ministério da Agricultura, Pecuária e Abastecimento) and for family farming by MDA. Consequently, the Brazilian government has attempted to present both as part of the Brazil–Africa Dialogue to enable African ministers to learn about the wide range of policies implemented in Brazil. Combined with demanddriven horizontal cooperation, the approach has enabled African countries to choose between (and sometimes combine) approaches to promoting their agriculture.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural; south-south cooperation / cooperação sul-sul

Brazil, biofuels, and food security in Mozambique - Thali, Kai (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
This chapter, therefore, explores the role of agriculture in Brazilian develop ment assistance programmes and direct investment in Africa, focusing on the potential tensions between biofuel feedstock and food production. After a brief overview of the history of Brazil’s own agricultural development and the country’s relations with Africa, the chapter delves into an examination of Brazilian engagement in the conjoined agricultural and energy sectors of Mozambique, a country that possesses large tracts of arable land and is considered a prime site for biofuel production. The chapter critiques Brazil’s development assistance and investment model and presents ways to improve its effectiveness in order to generate greater benefits for the Mozambican people.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; agriculture / agricultura

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

The Expansion of Tree Monocultures in Mozambique. Impacts on Local Peasant Communities in the Province of Niassa - Overbeek, Winfridus (Movimento Mundial pelas Florestas Tropicais, 2010)
This publication is the result of a visit to Mozambique in November 2009 by two activists involved in the struggle against tree monocultures in the Brazilian state of Espírito Santo. This visit was made possible by the World Rainforest Movement (WRM) with the goal of exchanging experiences about large-scale tree monocultures. With more than 40 years of dealing with monoculture plantations and expansion, Brazil has a lot of experience in this area. At the same time, affected communities and supporting organizations in the country have led several struggles and acts of resistance and formed alliances, which nearly ten years ago resulted in the foundation of the Alert against the Green Desert Network (Rede Alerta contra o Deserto Verde). In the past few years, WRM has been made aware of the fact that more and more tree monocultures are being planted in Mozambique. Since Brazil and Mozambique have in common Portuguese as their official language, the idea arose to promote the exchange between the two countries so as to: − exchange experiences with the affected communities about the impacts; − better understand the current situation of the introduction and expansion of tree monocultures in Mozambique; and, − identify organizations involved or interested in the subject. This visit would not have been possible without the invaluable help of our friends at UNAC (União Nacional de Camponeses - National Peasant Union) in Mozambique, and UCA (União dos Camponeses e Associações de Lichinga - Union of Peasant and Associations of Lichinga), who volunteered to receive and accompany the Brazilian delegation and organized the visits to the communities. We also want to thank Via Campesina Brasil for their support in this initiative.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado